BM study: a monocentric prospective observational cohort study on neonatal humoral immunity against COVID-19 secondary to transplacental antibody transfer and breastfeeding - Rosa Perretta; Juan José Borraz Torca; Giuseppina De Luca; Marta Donà; Martina Gasparella; Elisa Rizzato; Nicola Bertazza Partigiani (Italian Journal of Pediatrics)
Abstract Background The COVID-19 pandemic highlighted the vulnerability of pregnant women and newborns, emphasizing the importance of vaccination during pregnancy to protect mothers and their infants. Maternal vaccination generates robust anti-SARS-CoV-2 IgG antibodies, transferred to the fetus through the placenta, providing neonatal protection. Breastfeeding also transfers maternal antibodies (IgA and IgG), potentially enhancing mucosal immunity. This study aimed to evaluate neonatal antibody kinetics following maternal COVID-19 vaccination, comparing vaccinated naïve mothers to those previously infected. Methods A monocentric prospective observational cohort study was conducted between July 2021 and July 2022, enrolling 44 mother-infant pairs at the Pediatrics Unit of Arzignano Cazzavillan Hospital. Eligible participants included mothers vaccinated during pregnancy (third trimester), either naïve or previously infected with SARS-CoV-2. Blood and breast milk samples were collected at birth and periodically up to six months postpartum. Neonatal cord blood and subsequent samples were analyzed for anti-SARS-CoV-2 spike (S1) IgG and IgA antibodies. Statistical analyses involved parametric and non-parametric tests, with significance set at p < 0.05. Results Out of 44 enrolled pairs, 12 breastfeeding pairs (9 naïve and 3 previously infected mothers) and 3 formula-fed pairs completed the full protocol. At birth, neonates demonstrated significantly higher IgG levels than mothers, especially from naïve mothers, confirming efficient transplacental antibody transfer (p < 0.05). Breast milk from previously infected mothers contained significantly higher IgA levels than naïve mothers at all postpartum time points (p < 0.05), whereas IgG levels remained stable and similar between groups. Formula-fed infants exhibited a faster decline in serum IgG compared to breastfed infants. Conclusions Maternal vaccination during pregnancy induced robust transplacental IgG transfer, providing neonatal protection from birth. Breastfeeding significantly maintained neonatal IgG levels and contributed additional IgA-mediated mucosal protection, particularly following maternal infection. Formula-fed infants experienced a more rapid antibody decline. Maternal COVID-19 vaccination effectively transfers protective antibodies transplacental and through breastfeeding, suggesting its importance in prenatal care strategies.